Movement and counter-movement: a history of abortion law reform and the backlash in Colombia 2006-2014 - Ruibal, Alba (2014)
In 2006, the Constitutional Court of Colombia issued Decision C-355/2006, which liberalized the country’s abortion law. The reform was groundbreaking in its argumentation, being one of the first judicial decisions in the world to uphold abortion rights on equality grounds, and the first by a constitutional court to rule on the constitutionality of abortion within a human rights framework. It was also the first of a series of reforms that would liberalize the abortion regulation in four other Latin American countries. The Colombian case is also notable for the process of strategic litigation carried out by feminist organizations after the Court’s decision, in order to ensure its implementation and counter the opposition from conservative actors working in State institutions, as well as for the active role played by the Court in that process. Based on fieldwork carried out in Colombia in 2013, this article analyzes the process of progressive implementation and reactionary backlash after Decision C-355/2006, with an emphasis on strategic litigation by the feminist movement and subsequent decisions by the Constitutional Court, which consolidated its jurisprudence in the field of abortion rights. It highlights the role of both feminists and of conservative activists within State institutions as opposing social movements, and the dynamics of political and legal mobilization and counter-mobilization in that process.